(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2003)
Tomatoes (Lycopersicon esculentum Mill) and other vegetables, bean and fruits contain a number of phytonutrients, which are a useful source of energy, metabolic structural material and antioxidants. Additionally, they may boost the immune system or encourage enzymes that detoxify carcinogens. However, varietal productivity with regard to number of fruits per plant and quantity of phytonutrients is largely unknown. A pot experiment was conducted to analyse variety productivity and fruit phytonutrient contents (lycopene, beta-carotene and ascorbic acid such as contents and their relationships in 13 varieties of tomato. Ten varieties were obtained locally and 3 developed by USDA, viz. 97L63, 97L66 and 97L97 (with known high fruit beta-carotene and suited for use in processing applications). The seedlings raised in nurseries were later transplanted in pots (one plant per pot), 5 plants per variety. Lycopene and beta-carotene contents were analysed, using column chromatography and spectrophotometry. Ascorbic acid content was also analysed spectrophotometrically. The statistical analysis revealed that, Hyb-SC-3 and Hyb-Himalata varieties gave maximum fruit yield. Lycopene content was maximum in Anupamam and beta-carotene, in New Uday and all 3 USDA varieties. The variety New Uday also excelled in ascorbic acid content. The positive relationship (r = 0.99) between carotenoid biosynthesis and ascorbic acid content is not clear. Interestingly, the inverse correlation (r = -0.72) between beta-carotene and lycopene confirms that accumulation of beta-carotene in tomato occurs at the expense of lycopene as beta-carotene is downstream of lycopene in the biosynthetic pathway.